Magnetic flux leakage theories and imaging technologies - Huang, Songling; Zhao, Wei (Advances in Electrical and Electronic Engineering, 2016)
This book systematically introduces magnetic flux leakage testing principles and their applications in practice. Signal detection, collection, processing, the inversion of magnetic flux leakage defect and 3D imaging are discussed in detail with extensive project experiences, making the book an essential reference for researchers, developers and engineers in nondestructive testing